When a bigger brain is better: The case of bee olfactory learning - Coline Monchanin; Tamara Gómez-Moracho; Cristian Pasquaretta; Alexis Buatois; Louise Bestea; Paul Marchal; Philipp D. Lösel; Renaud Lebrun; Fabrice Lihoreau; Andrew B. Barron; Jean-Marc Devaud; Mathieu Lihoreau (Proceedings of the National Academy of Sciences, 2026)
Whether bigger brains provide enhanced cognitive capacities is a long-lasting and controversial question. While big brains may not be required for producing sophisticated behavior, they could facilitate information processing and memory storage. Here, we report a positive relationship between head size and learning performance in two model bee species, using data from 2,141 individuals. Among honey bees, head size varied by about 30%, and those with larger heads showed higher olfactory learning performance for associative tasks that varied in difficulty. Microcomputed tomography measures indicated that this relationship was linked to brain size variation: The best odor learners had the largest antennal lobes. We made similar observations in bumblebees, suggesting that natural brain size variation is associated with individual cognitive variation in these social bees.